2010
DOI: 10.1029/2009jd013017
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical and radiative properties of tropical clouds investigated in TC4 and NAMMA

Abstract: [1] The size, shape and concentration of ice particles in tropical anvil cirrus and in situ cirrus clouds have a significant impact on cloud radiative forcing, and hence on global climate change. Data collected in tropical anvil and cirrus clouds with a 2D-S probe, an optical imaging probe with improved response characteristics and the ability to remove shattered artifacts, are analyzed and discussed. The data were collected with NASA DC-8 and WB-57F research aircraft near Costa , ice water contents exceeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
186
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(216 citation statements)
references
References 81 publications
(112 reference statements)
27
186
3
Order By: Relevance
“…The average D (µm) of crystals (columns; plates; bullets) in non-anvil clouds (154.0; 122.3; 132.6) are larger than those in anvil clouds (109.8; 104.0; 99.9) during TWP-ICE, whereas those in anvil clouds (187.2; 117.5; 158.5) are larger than those in non-anvil clouds (158.1; 116.3; 132.8) during SPARTICUS at −67 < T < −35 • C. shows a strong dependence on the type of cirrus, and is much higher in anvil clouds compared to non-anvil clouds for TWP-ICE and SPARTICUS, which agrees with previous studies (e.g., Connolly et al, 2005;Um and McFarquhar, 2009;Lawson et al, 2010). In general, crystal dimensions are found to increase with temperature (e.g., Fig.…”
Section: Dependence On Geophysical Locations and Type Of Cirrussupporting
confidence: 82%
See 1 more Smart Citation
“…The average D (µm) of crystals (columns; plates; bullets) in non-anvil clouds (154.0; 122.3; 132.6) are larger than those in anvil clouds (109.8; 104.0; 99.9) during TWP-ICE, whereas those in anvil clouds (187.2; 117.5; 158.5) are larger than those in non-anvil clouds (158.1; 116.3; 132.8) during SPARTICUS at −67 < T < −35 • C. shows a strong dependence on the type of cirrus, and is much higher in anvil clouds compared to non-anvil clouds for TWP-ICE and SPARTICUS, which agrees with previous studies (e.g., Connolly et al, 2005;Um and McFarquhar, 2009;Lawson et al, 2010). In general, crystal dimensions are found to increase with temperature (e.g., Fig.…”
Section: Dependence On Geophysical Locations and Type Of Cirrussupporting
confidence: 82%
“…16). This is consistent with bulk ice sizes increasing with temperature as observed in situ (e.g., Lawson et al, 2010) and from satellite measurements (e.g., Yuan and Li, 2010;van Diedenhoven et al, 2014b). Furthermore, the general weak dependence of crystal aspect ratio on temperature shown in Fig.…”
Section: Dependence On Geophysical Locations and Type Of Cirrussupporting
confidence: 75%
“…The microphysical properties of mature deep convection updrafts remain poorly quantified, at least in part because of sparse in situ measurements available from aircraft campaigns, which provide the only direct means of measuring hydrometeor mixing ratio, morphology, size distribution, and phase within strong updrafts Stith et al 2002Stith et al , 2004Anderson et al 2005;Stith et al 2006;Lawson et al 2010). A glaring result is the lack of observational data adequate to quantitatively constrain order-of-magnitude differences in condensate mixing ratios commonly predicted by cloud-resolving simulations of deep convection systems using differing microphysics schemes, where interaction of dynamics and microphysics schemes likely contribute to differences (Varble et al 2011;Zhu et al 2012;Collis et al 2013;.…”
Section: Introduction a Motivationmentioning
confidence: 99%
“…Mitchell et al (2011) demonstrated that, for a given effective diameter and IWC, the optical properties of a PSD are sensitive to its shape. Therefore, PSD bimodality and concentrations of small ice crystals are critical to realistically parameterizing cirrus PSDs, to modeling their radiative properties and sedimentation velocities, and to mathematical forward models designed to infer cirrus PSDs from remote-sensing observations (Lawson et al, 2010;Mitchell et al, 2011;Lawson, 2011). In order to improve knowledge on PSD shape, as well as to develop statistical algorithms for correcting historical PSD datasets so that PSD shapes are corrected along with computations of bulk properties, it will be necessary to make use of instruments that can provide reliable measurements of small ice crystals beneath the size floors of both the 2DC and the 2D-S.…”
Section: Final Results and Discussionmentioning
confidence: 99%
“…The opposite is true for the 2DC. This is attributed to the 2D-S's larger sample volume; to its improvements in resolution and electronic time response over the 2DC; and to its 256 photodiode elements (Jensen et al, 2009;Lawson, 2011;Brenguier et al, 2013), which allow it to size particles smaller than 100 µm and to measure particle inter-arrival times more accurately (Lawson et al, 2010;Korolev et al, 2013b;Brenguier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%